Assessment of Apparent Diffusion Coefficient Values as Predictor of Aggressiveness in Peripheral Zone Prostate Cancer: Comparison with Gleason Score. (9th February 2014) - Anwar, Shayan Sirat Maheen; Anwar Khan, Zahid; Shoaib Hamid, Rana; Haroon, Fahd; Sayani, Raza; Beg, Madiha; Khattak, Yasir Jamil
Abstract : Purpose . To determine association between apparent diffusion coefficient value on diffusion-weighted imaging and Gleason score in patients with prostate cancer. Methods . This retrospective case series was conducted at Radiology Department of Aga Khan University between June 2009 and June 2011. 28 patients with biopsy-proven prostate cancer were included who underwent ultrasound guided sextant prostate biopsy and MRI. MRI images were analyzed on diagnostic console and regions of interest were drawn. Data were entered and analyzed on SPSS 20.0. ADC values were compared with Gleason score using one-way ANOVA test. Results . In 28 patients, 168 quadrants were biopsied and 106 quadrants were positive for malignancy. 89 lesions with proven malignancy showed diffusion restriction. The mean ADC value for disease with a Gleason score of 6 was 935 mm 2 /s (S D = 248.4 mm 2 /s); Gleason score of 7 was 837 mm 2 /s (S D = 208.5 mm 2 /s); Gleason score of 8 was 614 mm 2 /s (S D = 108 mm 2 /s); and Gleason score of 9 was 571 mm 2 /s (S D = 82 mm 2 /s). Inverse relationship was observed between Gleason score and mean ADC values. Conclusion . DWI and specifically quantitative ADC values may help differentiate between low-risk (Gleason score, 6), intermediate-risk (Gleason score, 7), and high-risk (Gleason score 8 and 9) prostate cancers, indirectly determining the aggressiveness of the disease.